2017
DOI: 10.1038/bjc.2017.372
|View full text |Cite
|
Sign up to set email alerts
|

Sox5 contributes to prostate cancer metastasis and is a master regulator of TGF-β-induced epithelial mesenchymal transition through controlling Twist1 expression

Abstract: Therefore, we propose a new mechanism in which Smad3/Sox5/Twist1 promotes EMT and contributes to PCa progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…SOX5 is a member of the SOX family of transcription factors and plays a critical role in the progression of various cancer types. It has been reported that SOX5 may regulate epithelial-mesenchymal transition (EMT) via altering the expression of the twist-related protein 1 (Twist1) and, consequently, facilitating metastasis in prostate cancer [40]. Besides, it has been found that SOX5 overexpression may reverse apoptosis induced by miR-132 and miR-15a/16 in pituitary tumor cells and that SOX5 is upregulated in invasive pituitary tumor tissues [41].…”
Section: Discussionmentioning
confidence: 99%
“…SOX5 is a member of the SOX family of transcription factors and plays a critical role in the progression of various cancer types. It has been reported that SOX5 may regulate epithelial-mesenchymal transition (EMT) via altering the expression of the twist-related protein 1 (Twist1) and, consequently, facilitating metastasis in prostate cancer [40]. Besides, it has been found that SOX5 overexpression may reverse apoptosis induced by miR-132 and miR-15a/16 in pituitary tumor cells and that SOX5 is upregulated in invasive pituitary tumor tissues [41].…”
Section: Discussionmentioning
confidence: 99%
“…After the secondary antibody was added dropwise, it was incubated at room temperature for 1 h, and after washing with PBS, the nuclei were stained with DAPI. The photograph was taken under an Olympus FV1000D confocal microscope [18].…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…The prepared cells were subjected to the YAP1 or TEAD1 CHIP assay using the EpiQuik Chromatin Immunoprecipitation Kit (Epigentek, Farmingdale, NY, USA) according to the protocol [18]. PCR was performed using primers specific for the YAP1 or TEAD1 binding regions in the SRC promoter.…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
“…There is evidence that creBBP is downregulated in Pca and is a tumor suppressor gene in small-cell lung cancer and other neuroendocrine tumors (63,64). Smad3/Sox5/Twist1 was reported to promote eMT and cancer progression in Pca (65). Mcc, a candidate tumor suppressor gene, was revealed to be often silenced by hypermethylation of its promoter in colorectal cancer (66).…”
Section: Discussionmentioning
confidence: 99%